Caudal Bupivacaine vs Bupivacaine plus Tramadol in post-operative Analgesia in Children - Shrestha, S K; Bhattarai, B (Journal of Nepal Health Research Council, 2011)
Background: Caudal analgesia with bupivacaine is used commonly for pain relief in children and extradural administration of tramadol seemed to be a safe method of analgesia. The aim of the study is to compare the analgesic efficacy of caudal bupivacaine and bupivacaine and tramadol mixture for postoperative analgesia and to observe for side effects. Methods: Fourty children, aged between 1- 6 years undergoing infra umbilical surgeries were selected for this randomized, control trial. They were randomly divided into two groups. Group A (n = 20) received 0.5 ml/kg of 0.25 % bupivacaine and Group B (n = 20) received 0.5 ml/kg of 0.25 % bupivacaine with 1 mg/kg of tramadol as a single shot caudal block. In the postoperative period heart rate, respiratory rate, pain score, recovery to first analgesic time, total number of analgesics required in 24 hours and side effects were noted and analyzed. Results: It was observed that the mean duration of pain relief was significantly longer in Group B (8.8 hrs Vs 7 hrs). Nausea and vomiting was observed in 25% of the patients in group B and 20 % of the patients in group A. None of the patients in both the groups had complication like motor weakness, urinary retention in the postoperative period. Conclusions: The addition of tramadol to bupivacaine in the caudal analgesic technique provides longer analgesia and lesser need for rescue analgesic in the postoperative period compared to bupivacaine.Â  Key words: caudal analgesia, bupivacaine, tramadol